PENEGAKAN HUKUM TERHADAP PELAKU PENYELENGGARA INVESTASI ILEGAL MENGGUNAKAN SKEMA PIRAMIDA - Dea Sufiani, (2022)
Illegal investment in the current era is very prevalent among the community, especially during the Covid 19 pandemic because investment is claimed to be able to make money easily by simply depositing the money on one of the investment platforms without measuring how the investment was made and what the investment material was. Many people do not know which investments are legal and illegal in accordance with the OJK permit. The investment prohibition is due to not having a permit and it is suspected that the investment uses an investment fraud scheme where the fraudulent scheme is a pyramid scheme. Legal action against illegal investments using a pyramid scheme can be subject to sanctions under Article 378 of the Criminal Code on fraud. However, positive law enforcement in Indonesia has not been widely implemented because the area being violated is in cyberspace, so there are still many other investment platforms circulating freely and continuing to deceive the public. This paper will discuss how the legal rules in Indonesia regarding illegal investments and the relationship between these investments and an investment fraud scheme. This study uses a normative juridical research method based on mapping the news as well as the existing laws and regulations. The results of this study are to provide understanding to the public so that they are not easily fooled by illegal investments because of the need for education to the public about the importance of knowing before investing.